MALIGNANT HYPERTENSION COMPLICATED BY RENAL THROMBOTIC MICRO ANGIOPATHY: ROLE OF ADAM 13 MUTATIONAL ANALYSIS - Aijazi, Ishma; Shama, Fadhil Al; Raman, Lakshmiah Ganapathy; Muhtiar, Sara (Journal of Ayub Medical College Abbottabad, 2017)
We report a case of a 38-year-old U.A.E national who presented with malignant hypertension and features of thrombotic microangiopathy. He presented with oliguria, renal failure, thrombocytopenia and haemolytic anaemia. He required several sessions of renal replacement therapy. ADAM 13 mutational analysis was sent to differentiate Thrombotic micro angiopathy due to thrombotic thrombocytopenic purpura (TTP) or malignant hypertension. Renal biopsy revealed histopathological features of malignant arteriolar nephrosclerosis (MANS). Haemolytic parameters improved after control of blood pressure and he was subsequently discharged with early nephrology follow up. Keywords: Malignant hypertension; Thrombotic Microangiopathy; MANS; Malignant arteriolar nephrosclerosis; Haemolytic uremic syndrome; HUS; Thrombotic thrombocytopenic purpura; TTP